2021
DOI: 10.4174/astr.2021.100.6.347
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for conservative treatment failure of right colonic diverticulitis

Abstract: Purpose Conservative treatment is the first-line therapy for acute colonic diverticulitis without severe complications, but treatment failure may increase hospitalization duration, medical costs, and morbidities. Usage of the modified Hinchey classification is insufficient to predict the outcome of conservative management. We aimed to investigate the clinical efficacy of the modified Hinchey classification and to evaluate predictive factors such as inflammatory markers for the failure of conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The rate of treatment failure was 1% Kim et al [ 26 ] RCS 2008–2009 Conservative treatment with antibiotics should be the treatment of choice for right-sided diverticulitis which had a recurrence rate of 13% Park et al [ 27 ] PCS 2007–2009 Outpatient management for uncomplicated right-sided diverticulitis had a similar recurrence rate compared with inpatient management (10% vs 11%, p = NS * ). No treatment failure was noted in both groups Park et al [ 20 ] PCS 2004–2012 The recurrence rate for medical treatment of right-sided diverticulitis was 19%; of those, diverticula located only in the right colon and a single diverticulum had a lower recurrence rate Park et al [ 19 ] RCS 2017–2019 In medical treatment for right-sided diverticulitis, 9% ended up with treatment failure. Elderly (Age > 50), recurrent episodes, and elevated C-reactive protein levels are factors associated with treatment failure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The rate of treatment failure was 1% Kim et al [ 26 ] RCS 2008–2009 Conservative treatment with antibiotics should be the treatment of choice for right-sided diverticulitis which had a recurrence rate of 13% Park et al [ 27 ] PCS 2007–2009 Outpatient management for uncomplicated right-sided diverticulitis had a similar recurrence rate compared with inpatient management (10% vs 11%, p = NS * ). No treatment failure was noted in both groups Park et al [ 20 ] PCS 2004–2012 The recurrence rate for medical treatment of right-sided diverticulitis was 19%; of those, diverticula located only in the right colon and a single diverticulum had a lower recurrence rate Park et al [ 19 ] RCS 2017–2019 In medical treatment for right-sided diverticulitis, 9% ended up with treatment failure. Elderly (Age > 50), recurrent episodes, and elevated C-reactive protein levels are factors associated with treatment failure.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported the details of antibiotic treatment: 7 with 2nd or 3rd generation of cephalosporin plus metronidazole [ 19 , 23 , 27 , 28 , 31 , 33 , 34 ] and 3 with adding aminoglycoside [ 22 , 26 , 36 ]. The duration ranged from 1 to 14 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations